已知2m^2+5n^2-4mn-2n-4m+5=0,求m+2n的值
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 09:15:57
已知2m^2+5n^2-4mn-2n-4m+5=0,求m+2n的值已知2m^2+5n^2-4mn-2n-4m+5=0,求m+2n的值 已知2m^2+5n^2-4mn-2n-4m+5=0,求m
已知2m^2+5n^2-4mn-2n-4m+5=0,求m+2n的值
已知2m^2+5n^2-4mn-2n-4m+5=0,求m+2n的值
已知2m^2+5n^2-4mn-2n-4m+5=0,求m+2n的值
已知m+n=-4 mn=2求mn
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=2,mn=1,求多项式(-2mn+2mn+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=4,mn=2,求多项式(-2mn+2m+3n)-(3mn+2n-2n)-(m+4n+mn)的值
已知m+n=-5,mn=4,求2(mn-3m)-3(2n-mn)
已知m-n=4,mn=2,求多项式(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值.
已知m-n=4,mn=-1,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=2,mn=1,求多项式(2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知|m-n-2|与(mn-1)^互为相反数,求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4n+mn)的值
已知m-n=3,mn=-3,求(-m-4n-mn)-(2mn-2m-3n)-(3mn+2n-2m)的值
已知m-n=3,mn=-1,求多项式-2mn+2m+3n-3mn-2n+2m-4n-m-mn的值
已知m-n=4,m、n互为倒数求(-2mn+2m+3n)-(3mn+2n-2m)-(m+4m+mn)的值
m-n=7 mn=-5求(3m+5n+4mn)-(2n-4n+6mn)
已知m-n=7,mn=-5,n=?根据m-n=7,mn=-5,求{3m-5n+4mn}-{2m-4n=6mn}的值
已知m-n=4,mn=1,则(2m+3n-2mn)-(m+4n)-(3mn+2n-2m)=_____
已知m分之一-n分之一=4,求2m-3mn-2n/m-2mn-n的值
已知1/m-1/n=2求m+4mn-n/2m-mn-2n的值